2009
DOI: 10.1111/j.1365-4632.2009.03991.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of androgen receptor gene as a candidate gene in female androgenetic alopecia

Abstract: In contrast with male AGA, no association was found between type II AGA in Egyptian women and the AR gene. Therefore, the genetic study of this gene does not serve as a biomarker for the identification of women with a predisposition to AGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
0
11
0
2
Order By: Relevance
“…The search strategy retrieved 65 potentially relevant studies. Based on the inclusion criteria, only 8 studies 7,8,12,24–28 with full text were included in this meta‐analysis, thus 57 studies were excluded. These 8 selected case–control studies had enrolled a total of 2074 patients with AGA and 1115 healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…The search strategy retrieved 65 potentially relevant studies. Based on the inclusion criteria, only 8 studies 7,8,12,24–28 with full text were included in this meta‐analysis, thus 57 studies were excluded. These 8 selected case–control studies had enrolled a total of 2074 patients with AGA and 1115 healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…No relationship has been found between the presence of the StuI restriction fragment and FPHL. 81 However, just as in men, the number of CAG repeats in the first exon of the AR gene was inversely correlated with FPHL. 82 , 83 This observation allowed the development of genetic testing, in which the detection of a small number of CAG repeats is associated with an increased risk of development of FPHL, whereas a larger number of repeats is associated with a lower risk ( http://www.hairdx.com ).…”
Section: Geneticsmentioning
confidence: 93%
“…Two other studies have investigated the association between the major M‐AGA susceptibility locus, the X‐chromosomal locus containing the androgen receptor ( AR ) and ectodysplasin A2 receptor ( EDA2R ) genes, and FPHL. These association studies, carried out in a very small Egyptian sample and the above‐mentioned sample of Chinese Han women with FPHL, were each limited to the investigation of the CAG repeat length variant of the AR gene and no association between this and FPHL was found . Fine mapping studies of this locus in AGA have indicated that the CAG repeat length variant is unlikely to be the causative variant and that other variants at this locus show much stronger association with AGA …”
Section: Heritable Factors—the Present Status Of Fphl Genetic Researchmentioning
confidence: 99%